Fable forest - Ng, Lui (Nanyang Technological University, 2022)
Language is political. Singapore’s language policies have shaped the way Singaporeans communicate – in English with a smattering of mother tongue – but also resulted in a distinct loss in dialect languages like Teochew. Yet, language conservation efforts were often predicated on the same models that oppressed them. Thus, Fable Forest approaches cultural and language conservation through sharing folktales, to enrich the readers’ minds with culture and knowledge, like a reforestation effort to a barren piece of land. Not unlike the roots of trees, we trace back to honour our history and form a stronger foundation for our personal and national identity.